DAKWAH SUFISTIK PERSPEKTIF KH. MOCH. DJAMALUDDIN AHMAD - Suhari; Slamet, Moh; Masruroh, Sayidah Afyatul (Universitas Hasyim Asy'ari (UNHASY) Tebuireng Jombang, 2025)
Indonesia, as the country with the largest Muslim population in the world, has vast potential for da’wah. However, the proliferation of religious activities has not fully reflected the success of da’wah in transforming people’s knowledge, attitudes, and behaviors according to Islamic teachings. This study focuses on the da’wah thought of KH. Moch. Djamaluddin Ahmad, or Yai Djamal, a charismatic scholar from Jombang known as a Sufi master and the caretaker of Pondok Pesantren Bumi Damai Al-Muhibbin. The research employs a library research method with a philosophical-qualitative approach to examine his thoughts, works, and da’wah practices. The findings reveal that Yai Djamal emphasizes Sufi-based da’wah through the transformation of Sufistic values along four main pathways: (1) practical Sufi education in daily life, (2) strengthening the role of pesantren as centers of Sufi education, (3) integrating Sufism into formal educational institutions, and (4) da’wah through religious gatherings, tarekat assemblies, and community routines. His Sufi-based da’wah thought has proven effective in shaping a religious society, strengthening spirituality, and fostering better social ethics. Thus, the Sufi-based da’wah of KH. Moch. Djamaluddin Ahmad makes a significant contribution to the development of an Islamic da’wah model that emphasizes morality, simplicity, and sustainable social transformation.